AnT²COK, an analytical model for cyclic oxidation kinetics of hot-work tool steels in transient thermal cycling conditions. (February 2019) - Dour, G.; Salem, M.; Le Roux, S.; Texier, D.; Medjedoub, F.; Lamesle, P.; Rézaï-Aria, F.
Highlights: Cyclic oxidation of hot work tool steel is studied based on thermal fatigue tests. Analytical model of cyclic oxidation is based on Arrhenius law and COSP-type models. The model extends the time-temperature equivalence to cyclic conditions. The model is relevant for any thermal cycles whether fully transient or with dwell. The model is applicable with step changes of activation energy or frequency factor. Abstract: In hot forming processes, steel tools are subjected to rapid temperature transients and cyclic oxidation. AnT²COK, a new analytical model based on diffusion-controlled oxide growth in cyclic conditions, is proposed to predict the parabolic oxidation kinetics in spallation-free conditions. Compared to cyclic oxidation models of the literature (COREST, COSP, DICOSM, etc.), it is applicable for any shape of thermal cycle, fully transient or with dwell time. The model is applied to thermal fatigue tests on X38CrMoV5 steel, for T max between 500 and 685 °C. Its validity is demonstrated above 550 °C, using frequency factor and activation energy calculated from isothermal tests.